Analisis Usability pada Aplikasi Trans Semarang dengan Metode Heuristics Evaluation - Puri Sulistiyawati; Abi Senoprabowo; Toto Haryadi (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
The Trans Semarang application is built by “UPTD”, the Public Service Agency of Trans Semarang to provide information about bus routes, ticket price, the nearest bus, and tourism. Referring to Playstore, there are a lot of complaints from users especially in difficulting usage of the application. This becomes a reason to evaluate the usability to find problems on user interface which is conducted through heuristic evaluation method by using the ten principles usability indicator. The result of this research is there are several problems, with the average of low problem by the low priority recovery and 2 aspects of problems with high priority recovery recommendation namely Consistency and Standard aspects with savering rating about 3,4. In addition, the results of this study are expected to be used as a reference and recommendation for developing the Trans Semarang application to make it easier and more comfortable for users.